Factors affecting unemployment among graduates in University Malaysia Kelantan - Karthika Siva Kumar; Laila Maisarah Zailani; Nur Syazwani Mohd Iazon Wan; Samihah Wan Azri (2024)
This study investigates the multifaceted factors contributing to the unemployment among graduates in University Malaysia Kelantan (UMK), concentrating on the independent variables of communication skills, employer preference, demanding attitude among graduates, and lack of career orientation where a thorough analysis is essential to discern the crucial factors that contribute to the elevated unemployment among graduates in UMK. The research focused on UMK graduates, specifically those from the Faculty of Entrepreneurship and Business (FEB), comprising a sample size of 250 individuals. Employing a convenience sampling method, data were collected and subsequent analysis was conducted using the SPSS software. The findings unveiled a compelling positive correlation between the percentage of unemployed UMK graduates and key independent variables, namely communication skills, demanding attitude among graduates, employer preference, and lack of career orientation. The study sheds light on the intricate dynamics affecting the employment prospects of UMK graduates and provides valuable insights for academia, policymakers, and stakeholders. Understanding the identified factors is crucial for developing targeted interventions and strategies to enhance the employability of UMK graduates in the competitive job market. This research contributes to the ongoing discourse on addressing unemployment challenges among university graduates, specifically focusing on the context of UMK in Kelantan, Malaysia.